Performance Variability of Islamic Banks and Sustainable Finance: Early and During the Pandemic: Variabilitas Performa Bank Islam dan Keuangan Berkelanjutan: Awal dan Selama Pandemik - Hartadinata, Okta Sindhu; Farihah, Elva; Hapsari, Meri Indri (Journal of Accounting Science, 2023)
This study aims to present empirical evidence related to the variability of the performance of Islamic banks and the interest of Islamic banks in responding to sustainable finance policies at the beginning (2020) and during the pandemic (2021). This study uses secondary data derived from financial reports, annual reports, sustainability reports, and Corporate Social Responsibility (SCR) reports of Islamic banking companies listed on the Indonesian Stock Exchange for 2020 – 2021. The data were analyzed by descriptive quantitative methods, which consisted of 2 stages, namely: analysis of performance variability and content analysis. The results of this study indicate that a low ROA calculation result, even a negative value, does not necessarily reflect poor performance because earnings management policies influence it. The results of the analysis of sustainable financial performance show that Islamic Commercial Banks have a high commitment to implementing sustainable finance. This research is expected to provide the implication that sharia principles in implementing bank business can make the financial performance of Islamic banks last during the pandemic. In addition, these principles align with the principles of sustainable finance, making it easier for banks to adopt them. The results of the assessment can be used as an evaluation for policymakers or the bank itself to achieve the best performance in carrying out sustainable finance practices and for interested parties to participate in supporting sustainable finance practices.